Knowledge as “wings” and resilience as “armor”: a study on the impact of civil aviation pilots’ personal knowledge management abilities on career resilience - Wu, Fan; Lai, Mimi; Li, Mingyang (Frontiers in Psychology, 2025)
BackgroundPilots bear the critical responsibility of ensuring the safe operation of civil aviation, and their level of occupational resilience directly impacts the sustainable development of civil aviation safety. Based on this, this study is grounded in the global context of civil aviation safety development and draws on Conservation of Resources Theory and social exchange theory to construct a theoretical model of how individual knowledge management capabilities influence the occupational resilience of civil aviation pilots.MethodsThe respondents in this study were recruited using random sampling methods, with questionnaires distributed online and offline between January and June 2025. The survey mainly covered pilots from China’s four major airline groups. Participants were asked to complete the Positive Personal Knowledge Management Ability Scale, Career Resilience Scale, Safety Behavior Scale, Safety Climate Scale, and Work Pressure Scale. A total of 210 valid questionnaire data from Chinese civil aviation pilots were collected.ResultsFirst, personal knowledge management ability significantly positively affects the career resilience of civil aviation pilots (β = 0.654, p < 0.001), and safety behavior plays a partial mediating role in the relationship between the two. Second, safety climate (β = −0.028, p < 0.05) and work stress (β = −0.026, p < 0.05) both showed an inverted U-shaped moderating effect on the influence of personal knowledge management ability on the career resilience of civil aviation pilots. Third, heterogeneity analysis found that the personal knowledge management ability of pilots from key universities (β = 0.773, p < 0.001) and domestic aviation colleges (β = 0.707, p < 0.001) had a stronger promoting effect on career resilience.ConclusionThe research results clarify the process mechanism by which personal knowledge management ability stimulates the career resilience of civil aviation pilots, enriches the study of personal career resilience, and provides theoretical and practical inspiration for ensuring civil aviation flight safety.